2017
DOI: 10.1063/1.4990569
|View full text |Cite
|
Sign up to set email alerts
|

Effective g factor of low-density two-dimensional holes in a Ge quantum well

Abstract: We report measurements of the effective g factor of low-density two-dimensional holes in a Ge quantum well. Using the temperature dependence of the Shubnikov-de Haas oscillations, we extract the effective g factor in a magnetic field perpendicular to the sample surface. Very large values of the effective g factor, ranging from ∼ 13 to ∼ 28, are observed in the density range of 1.4 × 10 10

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…5(d) (right panel), with the range of the g-factor being in good agreement with the fan diagram analysis and other reports in Ge 38 . The observed enhancement of the g-factor with decreasing densities has been previously observed and attributed to an increase in the strength of the effective Coulomb interaction 39,40 or to the non-parabolicity of the valence band 38 .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…5(d) (right panel), with the range of the g-factor being in good agreement with the fan diagram analysis and other reports in Ge 38 . The observed enhancement of the g-factor with decreasing densities has been previously observed and attributed to an increase in the strength of the effective Coulomb interaction 39,40 or to the non-parabolicity of the valence band 38 .…”
Section: Resultssupporting
confidence: 68%
“…Indeed, gate controlled quantum dots, ballistic 1D channels, and ballistic phase coherent superconductivity were demonstrated recently by using undoped Ge/SiGe. So far the added complexity in developing reliable gate‐stacks has limited the investigation of quantum transport properties in undoped Ge/SiGe to devices with mobilities significantly inferior compared to modulation‐doped structures …”
Section: Introductionmentioning
confidence: 99%
“…The mass is further reduced to 0.035m 0 for device alignment along the <100> direction 166 . Magnetotransport studies 9,167,170 confirmed that 2D holes in strained-Ge exhibit large out-of-plane effective g-factors, with a reported value 170 g * ⊥ ≈20 at a density below 1×10 11 cm −2 . Large spin-splitting energies (up to ≈ 1 meV) were observed 88-90, 139, 159, 161, 162, 164 due to a cubic Rashba-type spin-orbit interaction.…”
Section: Planar Heterostructuresmentioning
confidence: 89%
“…The superior quality achieved in reverse-graded Ge/SiGe heterostructures enabled a plethora of quantum transport studies in modulation-doped etched Hall-bar devices 89,141,[155][156][157][158][159][160][161][162][163][164][165][166][167][168] and, more recently, in undoped H-FETs 45,90,140,154,[169][170][171] . Initial expectations from bandstructure considerations were confirmed and the knowledge-base of confined holes in planar Ge was advanced.…”
Section: Planar Heterostructuresmentioning
confidence: 99%
“…17 The ability to manipulate qubit states by applying microwave electric fields directly to a quantum dot confinement electrode provides the possibility for simplified device layout schemes, in contrast to single-spin electron systems in silicon that have used onchip micromagnets or microwave striplines for qubit control. Further, the large out-of-plane gfactor of up to g ~ 28 in the two-dimensional Ge/SiGe system 22,23 means that a relatively small externally applied magnetic field can be used to set the rotation frequency and facilitate readout in a single spin-based qubit.…”
Section: Introductionmentioning
confidence: 99%